LAW AND PUBLIC POLICY - Fery Fery (Surakarta Law and Society Journal, 2019)
Many laws and regulations were chosen as a means to implement public policy. Therefore, in essence the law also contains values, concepts and goals. The realization of the objectives of public policy in the form of law is inseparable from the purpose of the law itself, namely to regulate society effectively.